Quercetin depletes intracellular Ca2+ stores and blunts ATP‐triggered Ca2+ signaling in bEnd.3 endothelial cells. (4th November 2019) - Chen, Cing‐Yu; Hour, Mann‐Jen; Shiao, Lian‐Ru; Wong, Kar‐Lok; Leung, Yuk‐Man; Chan, Paul; So, Edmund Cheung
Abstract: Quercetin is a flavonol polyphenol widely found in many vegetables, grains, and fruits. Quercetin has been shown to inhibit proliferation and invasion of various glioma cells and is regarded as a potential anticancer agent against glioma. However, whether and how this drug could affect brain blood vessels and endothelial cells (EC) are less understood. Further, there is hitherto no report on how quercetin affects brain EC Ca 2+ homeostasis. In this report, we investigated the effects of quercetin on Ca 2+ homeostasis in mouse brain bEnd.3 EC. We demonstrated that quercetin raised cytosolic Ca 2+ level in a concentration‐dependent manner. Quercetin‐triggered Ca 2+ signal composed of both internal Ca 2+ release and extracellular Ca 2+ influx. Quercetin caused Ca 2+ release from the endoplasmic reticulum, and consistently, inhibition of inositol 1, 4, 5‐trisphosphate receptor (IP3R) by xestospongin C (XeC) suppressed quercetin‐triggered Ca 2+ release. Quercetin also caused Ca 2+ release from lysosomes, an observation in concordance with the inhibition of quercetin‐triggered Ca 2+ release by trans ‐Ned‐19, a blocker of two‐pore channels. As quercetin depleted intracellular Ca 2+ storage, it suppressed ATP‐induced Ca 2+ release and thereby blunted ATP‐triggered Ca 2+ signaling. In addition, quercetin co‐treatment significantly suppressed ATP‐stimulated nitric oxide release. Our work therefore showed, for the first time, quercetin perturbed intracellular Ca 2+ stores and strongly suppressed ATP‐triggered response in bEnd.3 cells.